Evaluasi dalam Perspektif Pendidikan Islam - Mursal Aziz (Journal on Education, 2023)
Evaluation in an Islamic perspective has a unique purpose and is different from evaluation in the context of general education. The purpose of evaluation in an Islamic perspective is to measure the achievement of students in achieving educational goals based on Islamic values. This evaluation involves an assessment of the academic, moral, character and spiritual aspects of students. An effective evaluation will reveal the level of students' understanding of religious concepts, such as monotheism, morality, fiqh, Islamic history, and other moral principles. In addition, the evaluation also measures students' mastery of acts of worship such as prayer, fasting, zakat, and pilgrimage. Evaluation in Islamic education also aims to evaluate the moral and character development of students according to Islamic values. Evaluation results in Islamic education include an in-depth understanding of Islamic teachings. The results of this evaluation can provide information about the extent to which students understand and carry out worship correctly. The results of the evaluation will also show the attitude, behavior, integrity, honesty, fairness, patience and piety of students